2022 Roadmap on aqueous batteries. (1st October 2022) - Wu, Daxiong; Li, Xiu; Liu, Xiaoyu; Yi, Jin; Acevedo-Peña, Próspero; Reguera, Edilso; Zhu, Kai; Bin, Duan; Melzack, N; Wills, R G A; Huang, Jianhang; Wang, Xiaotong; et al.
Abstract: The development of efficient electrochemical energy storage devices is crucial for future renewable energy management. Aqueous rechargeable batteries (ARBs) are considered to be one of the most sustainable battery technologies due to their low cost, ease of manufacture, high safety and environmental friendliness. However, some tough issues, such as the narrow electrochemical stability window of water, chemical instability of electrode materials, uncontrollable dendrite growth and poor cycling lifespan, severely limit the development of high-energy aqueous batteries with stability and infallible safety. This article mainly summarizes current and future challenges and the advanced science and technology to meet these challenges of various ARBs, such as aqueous Li/Na/K/Mg/Ca/Al/-ion batteries, aqueous flow batteries and photo-responsive batteries. In addition, the potential direction and prospect of the further development of these system batteries are discussed. Finally, given the various technologies and their associated technical challenges, we are motivated to develop a 2022 roadmap on aqueous batteries.